Since they are both equal to then they are equal. This means
Now substitute each point into one of the equations to find the values.
Hi;
I have the equations y = 2x^2 - 2x +3 and y = x^2 + 5x -7 therefor they are both equal so set them equal and solve I'm ok with that but...
I thought I could set them both to zero and solve for x by elimination ie
2x^2 - 2x + 3 = 0
x^2 + 5x - 7 = 0
giving
2x^2 - 2x = -3
x^2 + 5x = 7
multiplt the second equation by 2
2x^2 - 2x = -3
2x^2 + 10x = 14
I thought this would let me eliminate the x^2 terms and solve for x but I get the wrong solution and I don't know why?
Thanks